Projective synchronization for a cass of 6-D hyperchaotic lorenz system - Ahmed S. Al-Obeidi; Saad Fawzi AL-Azzawi (Institute of Advanced Engineering and Science, 2019)
This paper is concerned with the projective synchronization problem for a class of 6-D nonlinear dynamical system which is called hyperchaotic Lorenz system when the parameters of this system are unknown. Based on scaling factor which belong to above strategy, four controller are proposed to achieve projective synchronization between two identical systems via using Lyapunov's direct method and nonlinear control strategy. These scaling factor taken the values, and 2 for each control respectively. A numerical simulations are used to demonstrate the efficiency of the proposed controller.